Testicular transcriptional signatures associated with high fertility. Issue 2 (February 2018) - Michaelis, Marten; Sobczak, Alexander; Koczan, Dirk; Langhammer, Martina; Reinsch, Norbert; Schön, Jennifer; Weitzel, Joachim M
Abstract : Abstract: Factors of high fertility are poorly described. The majority of transgenic or knockout models with a reproductive phenotype are subfertile or infertile phenotypes. Few genotypes have been linked to improved reproductive performance (0.2%) or increased litter size (1%). In this study, we used a unique mouse model, fertility line FL1, selected for 'high fertility' for more than 170 generations. This strain has almost doubled the number of littermates as well as their total birth weight accompanied by an elevated ovulation rate and increased numbers of corpora lutea compared to a randomly mated and unselected control line (Ctrl). Here, we investigate whether the gonadal tissue of FL1 males are affected by 'co-evolution' after more than 40 years of female-focused selection. Using microarrays, we analysed the testicular transcriptome of the FL1 and Ctrl mice. These data were also compared with previously published female gonadal transcriptional alterations. We detected alterations in testicular gene expression, which are partly associated with female reproductive performance. Thus, female-focused selection for litter size has not only affected the female side, but also has been manifested in transcriptional alterations on the male gonadal organ. This suggests consequences for the entire mouse lines in the long run and emphasizes the perspective of inevitably considering both genders about mechanisms of high fertility.